2021
DOI: 10.1038/s41594-021-00656-9
|View full text |Cite
|
Sign up to set email alerts
|

Structures of outer-arm dynein array on microtubule doublet reveal a motor coordination mechanism

Abstract: Thousands of outer-arm dyneins (OADs) are arrayed in the axoneme to drive a rhythmic ciliary beat. Coordination among multiple OADs is essential for generating mechanical forces to bend microtubule doublets (MTDs). Using electron microscopy, we determined high-resolution structures of Tetrahymena thermophila OAD arrays bound to MTDs in two different states. OAD preferentially binds to MTD protofilaments with a pattern resembling the native tracks for its distinct microtubule-binding domains. Upon MTD binding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(121 citation statements)
references
References 74 publications
5
79
3
Order By: Relevance
“…The sparse microtubule decoration meant that typical microtubule reconstruction techniques [Zhang and Nogales, 2015;Cook et al, 2020] could not be used to solve the structure. Furthermore, applying conventional single particle analysis techniques was unsuccessful due to the dominating signal of the microtubule, as was observed previously by cryo-ET [Grotjahn et al, 2018] and in cryo-EM of axonemal dyneins bound to microtubule doublets [Ma et al, 2019;Walton et al, 2021;Kubo et al, 2021;Rao et al, 2021]. To overcome this, we developed a pipeline (described below) to subtract the microtubule signal from the micrographs (Figure 1A), which ultimately allowed us to successfully align the complexes (Figure 1B).…”
Section: A Microtubule-subtraction Pipeline To Solve Microtubule-boun...mentioning
confidence: 99%
“…The sparse microtubule decoration meant that typical microtubule reconstruction techniques [Zhang and Nogales, 2015;Cook et al, 2020] could not be used to solve the structure. Furthermore, applying conventional single particle analysis techniques was unsuccessful due to the dominating signal of the microtubule, as was observed previously by cryo-ET [Grotjahn et al, 2018] and in cryo-EM of axonemal dyneins bound to microtubule doublets [Ma et al, 2019;Walton et al, 2021;Kubo et al, 2021;Rao et al, 2021]. To overcome this, we developed a pipeline (described below) to subtract the microtubule signal from the micrographs (Figure 1A), which ultimately allowed us to successfully align the complexes (Figure 1B).…”
Section: A Microtubule-subtraction Pipeline To Solve Microtubule-boun...mentioning
confidence: 99%
“…45 unique non-tubulin proteins of CA were identified by combining previously published mass spectrometry data (46, 47), structure prediction by Phyre2, and sequence pattern search using own scripts (86). First, each of the subunits that show clear backbones was manually built as a poly-Ala model in the local regions with the best resolutions in Coot (87, 88).…”
Section: Methodsmentioning
confidence: 99%
“…Whether it forms a homodimer or heterodimer with another light chain remains to be confirmed, although there is evidence to suggest that, unlike the other light chains, the DYNLT2B subunit may be monomeric ( DiBella et al, 2001 ). Recent structural studies of Tetrahymena ODAs have revealed a Tctex-family heterodimer ( Rao et al, 2021 ).…”
Section: Cytoplasmic Dyneinsmentioning
confidence: 99%